Analisis Pengaruh Return On Asset, Debt To Equity Ratio, Firm Size, Current Ratio, Dan Growth Terhadap Pembayaran Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2012 - Isa Febrianti; Djuma hir (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect of Return On Asset (ROA), Debt Equity Ratio (DER), Firm Size, Current Ratio, and Growth on Dividend Policy (Studies in Manufacture Companies that listed in BEI over period 2009-2012). Types of research used in this research is explanatory research (research explanation) that aims to explain the causal relationship between the causal variables through hypothesis testing. The sampling technique used was census sampling and obtained a sample of 27 companies. To test the hypothesis proposed in this study used regression analysis. Regression analysis showed that ROA, Current Ratio, and Growth as well as have a significant influence on dividend policy, meanwhile DER and Firm Size have not a significant influence on dividend policy. Based on these results, investors can make profitability, liquidity, and growth as reference in predicting the value of dividend policy by companies.Keywords: Return On Asset (ROA), Debt Equity Ratio (DER), Firm Size, Current Ratio, and Growth Dividend Policy